NiAl-layered double hydroxide intercalated with Keggin polyoxometalate as adsorbent of malachite green: kinetic and equilibrium studies. Issue 5 (4th May 2022) - Palapa, N. R.; Taher, T.; Mohadi, R.; Rachmat, A.; Mardiyanto, M.; Miksusanti, M.; Lesbani, A.
Abstract: In this study, we attempted to intercalate the Keggin polyoxometalate (POM) anion SiW12 O40 4− with NiAl-layered double hydroxide using a facile ion-exchange technique under a N2 atmosphere. The obtained solids were characterized via X-ray diffraction analysis, Fourier-transform infrared spectroscopy, N2 adsorption-desorption isotherms, scanning and transmission electron microscopes to evaluate their surface morphology. Furthermore, the synthesized materials were employed as novel adsorbents for the removal of malachite green (MG) dye from aqueous solutions. The intercalation was successful. The synthesized material as an adsorbent for the removal of MG can be used for the removal of cationic dyes from aqueous solutions. The adsorption kinetics study showed that the adsorption of MG onto NiAl-POM best fitted the pseudo-second-order model, which indicated that the adsorption process was conducted chemically. Moreover, the adsorption isotherm revealed that the adsorption occurred in a monolayer system. The regeneration process showed that the high effectivity adsorption process after fifth cycles adsorption for NiAl-POM.